Solvent Additive Effects on Small Molecule Crystallization in Bulk Heterojunction Solar Cells Probed During Spin Casting. (4th September 2013) - Perez, Louis A.; Chou, Kang Wei; Love, John A.; van der Poll, Thomas S.; Smilgies, Detlef‐M.; Nguyen, Thuc‐Quyen; Kramer, Edward J.; Amassian, Aram; Bazan, Guillermo C.
<x xml:space="preserve">Abstract</x> Solvent additive processing can lead to drastic improvements in the power conversion efficiency (PCE) in solution processable small molecule (SPSM) bulk heterojunction solar cells. In situ grazing incidence wide‐angle X‐ray scattering is used to investigate the kinetics of crystallite formation during and shortly after spin casting. The additive is shown to have a complex effect on structural evolution invoking polymorphism and enhanced crystalline quality of the donor SPSM. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>